2012
DOI: 10.2217/pgs.11.175
|View full text |Cite
|
Sign up to set email alerts
|

CDA Deficiency as a Possible Culprit for Life-Threatening Toxicities After Cytarabine Plus 6-Mercaptopurine Therapy: Pharmacogenetic Investigations

Abstract: We describe here the case of a 7-year old girl with lymphoma who developed life-threatening toxicities upon cytarabine plus mercaptopurine. Surprisingly, initial investigations on canonical thiopurine methyltransferase genetic polymorphism proved to be negative. We focused next on deregulations affecting the CDA gene implicated in the liver disposition of cytarabine. This patient was homozygous for both the 79A>C and the -31delC polymorphisms on the CDA gene and promoter, two genotypes with reported opposite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Case reports in children suggest PM CDA status is predictive of Ara-C toxicity, but to date, no such relationship has been investigated in adults. 24 Here we establish for the first time the link between CDA phenotype and incidence of severe toxicities in adult patients with AML treated with Ara-C.…”
Section: Introductionmentioning
confidence: 75%
“…Case reports in children suggest PM CDA status is predictive of Ara-C toxicity, but to date, no such relationship has been investigated in adults. 24 Here we establish for the first time the link between CDA phenotype and incidence of severe toxicities in adult patients with AML treated with Ara-C.…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, Bhatla et al (2009) have shown that Ara-C-related mortality was significantly elevated in carriers of the 79CC genotype in children with acute leukemia. Moreover, Ciccolini et al (2012) have related this SNP to life-threatening toxicities induced in a girl with lymphoma treated with Ara-C.…”
Section: Cytosine Arabinosidementioning
confidence: 99%
“…Increased activity and expression of CDA was shown in AML patients who are nonresponders to induction chemotherapy when compared with those who respond well to Ara-C [10,11]. On the other hand, low CDA activity and expression has shown associated with severe drug-related toxicities [12,13]. NT5C2 opposes DCK activity by dephosphorylating the monophosphorylated form of drug back to Ara-C.…”
mentioning
confidence: 99%